Associação clínica dos sintomas defecatórios em mulheres com disfunção do assoalho pélvico - Vasconcelos Neto, José Ananias (2017)
Posterior vaginal wall prolapses have often been implicated in bowel symptoms, but the data are controversial. Objectives: The aim of this study was to evaluate the association and correlation of Bp point, perineal body (Pb) and genital hiatus (Gh) measures with constipation, anal incontinence, severity of symptoms and quality of life. Methods The patients were distributed into 2 groups according to the posterior vaginal wall Bp point (POP-Q): One group without posterior vaginal wall prolapse (Control Group = Bp ≤ -1) and one with posterior vaginal wall prolapse (Case Group = Bp ≥ 0). Demographic data, defecatory dysfunctions and SF-36 were compared between the groups. Correlations between severity of posterior prolapse (Bp, Gh, Pb and Gh+Pb) and severity of bowel symptoms were also calculated. Results A total of 613 women were evaluated, with 174 included (Control Group=69/39.7%, Case Group=105/60.3%). The groups were similar in the following characteristics: anal incontinence, fecal urgency and/or constipation. There was no correlation between the severity of constipation and anal incontinence, according to Wexner scores, and the severity of the posterior vaginal wall prolapse, measured through the Bp point. There were, however, statistically significant differences between the groups when comparing Pb, Gh and Gh+Pb measures. The Pb and Gh+Pb correlated positively with symptoms of constipation, as well as with the scores of some domains of the SF-36, however, there was no correlation with anal incontinence. Conclusion: These results suggest that the severity of posterior vaginal wall prolapse is not correlated with constipation or anal incontinence, but Pb and Gh + Pb measurements are correlated with constipation and SF-36 scores. Keywords: